KOMUNIKASI SEBAGAI PRAXIS: PENERAPAN TEORI HABERMAS DALAM GERAKAN SOSIAL MEDIA DIGITAL - Junus Kwelju; Rido Dominggus Latuheru (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
This article explores the application of Jurgen Habermas' critical communication theory in the context of digital media social movements. Using literature study and observation methods, this research analyzes how the principles of communication as praxis can be applied in the use of social media by social movements, focusing on a case study of the Black Lives Matter movement. The results of the discussion show that this movement has utilized social media as a discursive space to build critical awareness, spread alternative narratives, and facilitate open and inclusive dialogue, in accordance with Habermas' concept of ideal communication. However, the application of Habermas' theory also faces challenges, such as polarization, the spread of misinformation, and limited access. This article concludes that by creating a virtual public space that is inclusive and free from domination, digital media social movements can promote democratic values and social justice. However, more reflective and inclusive communication strategies, as well as cooperation with social media platforms, are needed to overcome these challenges. In the long run, the application of Habermas' theory can help create a more democratic digital environment and encourage transformative social praxis.